Ultrasound-chilling assisted annealing treatment to produce a lower glycemic index of white rice grains with different amylose content - Kannika Kunyanee; Tai Van Ngo; Sandra Kusumawardani; Naphatrapi Lungsakul (Ultrasonics Sonochemistry, 2022)
White rice samples, Chai-Nat1 (CN1) and Jasmin rice (KDML105), were treated with the ultrasound-chilling (UC) and combined with annealing treatments (UC + ANN 45, UC + ANN50, and UC + ANN55). Their physicochemical properties and in vitro glycemic index of rice samples were analyzed. UC + ANN treatments presented pasting temperature, gelatinization temperature and crystallinity increased whereas the glycemic index of both rice samples was decreased as compared to its native. Especially, UC + ANN55 treated rice produced the lowest glycemic index and starch hydrolysis. Moreover, UC + ANN treated CN1 rice exhibited delayed gelatinization temperature, increased gelatinization enthalpy, and decreased glycemic index than KDML105 rice. In addition, Pearson's correlation presented that UC + ANN and amylose content had a highly negative correlation with the glycemic index at p < 0.0.1. The result exhibited that UC followed by ANN show an effective way to modify starch granules with delayed starch hydrolysis reduced glycemic index and properties depending on annealing temperature and rice cultivar.
Keywords: Food composition and properties; Microbial Metabolites in Food Biotechnology; GABA and Rice Research